The evaluation of off-loading using a new removable oRTHOsis in DIABetic foot (ORTHODIAB) randomized controlled trial: study design and rational. Issue 1 (December 2016) - Mohammedi, Kamel; Potier, Louis; François, Maud; Dardari, Dured; Feron, Marilyne; Nobecourt-Dupuy, Estelle; Dolz, Manuel; Ducloux, Roxane; Chibani, Abdelkader; Eveno, Dominique-François; Crea Avila, Teresa; Sultan, Ariane; et al.
Abstract Background Off-loading is essential for diabetic foot management, but remains understudied. The evaluation of Off-loading using a new removable oRTHOsis in DIABetic foot (ORTHODIAB) trial aims to evaluate the efficacy of a new removable device "Orthèse Diabète " in the healing of diabetic foot. Methods/design ORTHODIAB is a French multi-centre randomized, open label trial, with a blinded end points evaluation by an adjudication committee according to the Prospective Randomized Open Blinded End-point. Main endpoints are adjudicated based on the analysis of diabetic foot photographs.Orthèse Diabète is a new removable off-loading orthosis (PROTEOR, France) allowing innovative functions including real-time evaluation of off-loading and estimation of patients' adherence. Diabetic patients with neuropathic plantar ulcer or amputation wounds (toes or transmetatarsal) are assigned to one of 2 parallel-groups:Orthèse Diabète or control group (any removable device) according to a central computer-based randomization. Study visits are scheduled for 6 months (days D7 and D14, and months M1, M2, M3, and M6). The primary endpoint is the proportion of patients whose principal ulcer is healed at M3. Secondary endpoints are: the proportion of patients whose principal ulcer is healed at M1, M2 and M6; the proportion of patients whose initial ulcers are all healed at M1, M2, M3, and M6; principal ulcer area reduction; time-related ulcer-free survival; development of new ulcers; new lower-extremity amputation; infectious complications; off-loading adherence; and patient satisfaction. The study protocol was approved by the French National Agency for Medicines and Health Products Safety, and by the ethics committee of Saint-Louis Hospital (Paris). Comprehensive study information including a Patient Information Sheet has been provided to each patient who must give written informed consent before enrolment. Monitoring, data management, and statistical analyses are providing by UMANIS Life Science (Paris), independently to the sponsor. Since 27/10/2013, 13 centres have agreed to participate in this study, 117 participants were included, and 70 have achieved the study schedules. The study completion is expected for the end of 2016, and the main results will be published in 2017. Conclusion ORTHODIAB trial evaluates an innovating removable off-loading device, seeking to improve diabetic foot healing (ClinicalTrials.gov identifier:NCT01956162 ).